Evaluation of long term trends in oxide of nitrogen concentrations in the Klang Valley region, Malaysia - Mohamed Elnour Yassen; Jamaluddin Md. Jahi; Shaharuddin Ahmad (Environmental Management Society, Malaysia, 2005)
Anthropogenic emissions of NOx account for a large majority of all nitrogen inputs to the environment. The major sources of man-made NOx emissions are high-temperature combustion processes such as those that occur in automobile and power plants. NOx contribute to a wide range of environmental effects directly and when combined with other precursors in acid rain and ozone. NOx react in the air to form ground-level ozone and fine particle pollution, which are associated with adverse health effects. Principally, and for a long time, transport vehicles and industrial emissions are the major sources of the pollutants emitted in the Klang Valley atmosphere. Following the increase of urbanization and industrialization, the amount of traffic has increased in the Klang Valley. Traffic is considered as the major source of NOx in the Klang Valley. Exhaust emissions from the petrol-powered motor vehicles include carbon monoxide, nitrogen oxide, hydrocarbons and particulate matter. A time series analysis of NOx monitoring data from six locations in the Klang Valley Region from 1997 to 2002 is presented. The aim of this study is to evaluate the variations and trends in NOx in the Klang Valley Region for the period 1997-2002. On an hourly and daily average basis, annual, seasonal, monthly and diurnal variations and trends in NOx concentrations are presented. The overall average daily concentration of NOx ranged from 0.03 ppm to 0.18 ppm, with maximums of about 0.32 ppm in Kuala Lumpur, with 98th percentiles in the range 0.17-0.28 ppm. It is of particular interest that all stations in 1997 showed high NOx concentrations due to haze episode. The highest level of NOx recorded in 1997 was 0.3 ppm in Kuala Lumpur. Variations in NOx were dominated by one daily peak at the morning rush hours and secondary peak in late evening. This suggests that the level of NOx during peak hour is higher and it can be attributed to the increase in traffic volume. In the Klang Valley Region, tremendous growth of motor vehicles has resulted in increasing CO and NOx emissions. Therefore, the role of source controls over emissions is stressed as a key management tool especially in relation to road transportation